2021
DOI: 10.18632/oncotarget.27906
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inflammatory microenvironment and hepatic macrophage subsets in experimental hepatocellular carcinoma models

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. HCC typically develops on a background of chronic inflammation and fibrosis with tumor associated macrophages (TAMs) playing an important role in chronic inflammation-induced HCC and progression. However, the liver harbors unique macrophages, resident liver Kupffer cells (KCs) and monocyte-derived macrophages (Mo-Mφ), and their contribution to HCC and to the population of TAMs is incompletely known. Here, we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Specifically, IL-1β instigated the pro-migratory effect of M2 cells, and FAO was responsible for the upregulated secretion of IL-1β, which depended on ROS and NLRP3 inflammasome [ 75 ]. A study on the diethylnitrosamine (DEN)-induced model of carcinogenesis engaged in transcriptomic analysis and demonstrated that MoMϕs acquire a proinflammatory phenotype during carcinogenesis in this model, which is, however, distinct from the mixed pro-inflammatory and immunosuppressive phenotype of cells from the NASH-induced carcinogenesis model [ 76 ]. This observation implies that there are diverse mechanisms in the response of immune cells to liver carcinogenesis in different animal models.…”
Section: The Role Of Macrophages In Hcc Pathogenesismentioning
confidence: 99%
“…Specifically, IL-1β instigated the pro-migratory effect of M2 cells, and FAO was responsible for the upregulated secretion of IL-1β, which depended on ROS and NLRP3 inflammasome [ 75 ]. A study on the diethylnitrosamine (DEN)-induced model of carcinogenesis engaged in transcriptomic analysis and demonstrated that MoMϕs acquire a proinflammatory phenotype during carcinogenesis in this model, which is, however, distinct from the mixed pro-inflammatory and immunosuppressive phenotype of cells from the NASH-induced carcinogenesis model [ 76 ]. This observation implies that there are diverse mechanisms in the response of immune cells to liver carcinogenesis in different animal models.…”
Section: The Role Of Macrophages In Hcc Pathogenesismentioning
confidence: 99%
“…DEN is an alkylating agent of DNA bases that induces gene expression patterns in mouse tumours that resemble the poor prognosis subclass of human liver cancer [ 148 , 149 ]. Therefore, DEN combined with an LDE diet is often used to feed mice to reproduce the HCC model.…”
Section: Current In Vivo Models Of Aldmentioning
confidence: 99%
“…CLD is associated with a shift in hepatic MF populations [ 59 , 60 , 125 , 126 , 127 , 128 ]. When liver MFs are exposed to high concentrations of damage-associated molecular patterns (DAMPs)/MAMPs, they polarize towards a pro-inflammatory phenotype, resulting in subsequent attraction of other inflammatory cells through the production of pro-inflammatory cytokines and chemokines ( Figure 1 ) [ 37 , 39 , 129 ].…”
Section: Macrophages During Gut-liver Axis Disruption In Chronic Liver Diseasementioning
confidence: 99%
“…We and others showed that HCC is characterized by KC depletion and a simultaneous rise of MoMFs, at least in mice [ 60 , 362 , 363 ]. However, we also showed that, in addition to the widely accepted contribution of infiltrating MoMFs to the TAM pool in HCC, KCs also express markers that are typically associated with TAMs [ 128 ]. The group of Ye et al recently showed that inhibition of monocyte-to-TAM differentiation leads to expansion of a pro-tumorigenic KC-like TAM population [ 364 ].…”
Section: Macrophages During Gut-liver Axis Disruption In Chronic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation